(untitled) (Praxis Educativa, 2016)
This article tries to analyze the presence of Human Rights in the syllabus of Citizenship Education (Civics) of some Latin American countries. Thus, in this way, it detects the conceptions of citizen and citizenship supported; it reveals the rights the curriculum places emphasis on, and identifies the relationships between Human Rights and some citizenship categories which are essential as equality and personality development, freedom, democracy, justice and social protection, national identity and diversity respect, coexistence and international interdependence, peace valuation and the instruments to solve conflicts, security and protection of the environment. With this aim, the theory is related to the relationship between citizenship and human rights and how this relation is expressed in the curricular area. In second place, a “Matrix of Citizenship Categories” is applied to the curriculum guidelines to determine, in this way, convergences and divergences and mainly, to detect the tendencies that are observed in the treatment of Human Rights in the syllabus. Finally, the text points some suggestions about new aims of citizens training looking at the future, where Human Rights take a central place.